Plant Physiological Assessments on Promising New HLB-Tolerant Citrus Rootstocks after Inoculation with the Phytopathogenic Ascomycete Rosellinia necatrix - Juan M. Arjona-López; Frederick G. Gmitter; Estefanía Romero-Rodríguez; Jude W. Grosser; José Luís Cantero-Sánchez; Carlos J. López-Herrera; Francisco J. Arenas-Arenas (Horticulturae, 2023)
Citriculture is considered the most important fruit industry and involves the cultivation of several fruit varieties, which are susceptible to many plant pathogens. In this sense, soil-borne pathogenic fungi, such Rosellinia necatrix, threaten citrus fruit production worldwide because they can cause fruit loss. Therefore, we assayed the physiological reaction of novel citrus rootstocks against white root rot disease during long-term management. Data from above-ground symptoms and chlorophyll content were periodically obtained during the experimental process. In addition, plant leaf area and percentage of biomass reduction were determined for each rootstock when the experiment finished. The behavior of the inoculated tolerant rootstocks was as follows: the lowest symptom rate of SAUDPC was achieved by B11R5T25 and N40R3T25; AMB+CZO manifested the highest disease incidence; B11R5T25 and A+VOLK × Orange 19-11-8 displayed the highest and the lowest chlorophyll content, respectively; AMB+CZO and A+VOLK × Orange 19-11-8 showed the highest biomass reduction, and the lowest was detected in B11R5T25 and N40R2T19; concerning the leaf area, N40R1T18, N40R3T25 and N40R2T19 showed the lowest response, and 2247 × 2075-01-2 achieved the highest rate. In summary, B11R5T25 and N40R3T25 displayed the lowest disease rate.